Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1354/vp.44-6-814
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Density of Clostridium difficile Toxin Receptors on the Intestinal Mucosa of Neonatal Pigs

Abstract: Abstract. Clostridium difficile is an enteric pathogen affecting a variety of mammals, but it has only recently been diagnosed as a cause of neonatal typhlocolitis in pigs. The most important virulence factors of C. difficile are 2 large exotoxins, toxin A (TcdA) and toxin B (TcdB). TcdA is a potent enterotoxin with effects on host tissues that are dependent upon receptor-mediated endocytosis of the intact toxin. TcdB is an effective cytotoxin, but it apparently does not bind receptors on intact mucosal epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 31 publications
2
35
1
Order By: Relevance
“…In human beings, the colon is the main site of C. difficile infection, but receptors for CD toxins have been isolated from the human small bowel, with substantial variability in small bowel toxin binding among individuals [1]. Animal studies have demonstrated C. difficile induced enteritis because of binding of toxin A to receptors in the small bowel [11][12][13]. In addition, as was demonstrated previously in transplanted human intestinal xenografts [14], C. difficile toxin B is a potent inflammatory enterotoxin and may contribute to intestinal damage in CDE.…”
Section: Discussionmentioning
confidence: 99%
“…In human beings, the colon is the main site of C. difficile infection, but receptors for CD toxins have been isolated from the human small bowel, with substantial variability in small bowel toxin binding among individuals [1]. Animal studies have demonstrated C. difficile induced enteritis because of binding of toxin A to receptors in the small bowel [11][12][13]. In addition, as was demonstrated previously in transplanted human intestinal xenografts [14], C. difficile toxin B is a potent inflammatory enterotoxin and may contribute to intestinal damage in CDE.…”
Section: Discussionmentioning
confidence: 99%
“…Purification of Toxins and Recombinant Fragments-TcdA and TcdB were isolated from C. difficile strain 10463 (ATCC, Manassas, VA) as described previously (65) and were stored in 50 mM Tris-HCl buffer, pH 7.5, at 4°C. Recombinant fragments of TcdA (amino acid residues 2304 -2710) and TcdB (amino acid residues 2286 -2366), which are fragments of the RBD, were cloned (as a BamHI-HindIII fragment for tcdA and a BamHI-EcoRI fragment for tcdB) into pTrcHisB (Invitrogen), transforming E. coli DH5␣MCR.…”
Section: Methodsmentioning
confidence: 99%
“…difficile is also associated with disease in animal species, including swine, calves, and horses (11,23,30). Extensive work has been conducted to describe C. difficile disease in swine; however, published data on the epidemiology and molecular characterization of C. difficile from swine herds is limited (9,30,33,35,37).…”
mentioning
confidence: 99%